The Relationship of Parenting Patterns with Events Early Marriage in Kepahiang District - Yuniwarti Yuniwarti; Hamzah Hasyim; Nur Alam Fajar; Muhammad Uyun (Budapest International Research and Critics University, 2021)
Early marriage is when children or teenagers are not, yet adults or teenagers aged 10–19 years old when they get married. Parents' critical role as the smallest and most immediate part of their teenagers' environment is expected to shape their character and personality to avoid early marriage decisions. According to survey data from the Kepahiang Regency's Ministry of Religion, there were 127 cases of marriages between people aged 19 and September 2021. This number increased compared to the 111 cases of early marriage reported in 2020, a 6.7 percent increase. The purpose of this study is to examine the factors that contribute to early marriage among pregnant women in Kepahiang Regency in 2021. and parenting styles. The study employed a cross-sectional design. This study surveyed pregnant women in Kepahiang Regency, with a sample size of 66 respondents. The analysis revealed no statistical significance between the respondents' education (p-value = 0.961). In addition, there was statistical significance for the father's education (p-value = 0.012). Furthermore, there was a statistical significance between the mother's education (p-value = 0.009). In addition, there was a statistical significance between income (p-value = 0.016). There is a statistical significance between parenting styles (p-value = 0.026). In addition, there is a statistical significance between respondents' knowledge (p-value = 0.030). Finally, the most dominant factor related to early marriage is the respondent's knowledge, with PR = 7,532 (95% CI; 1. 858-30,543), which means that respondents with more minor and moderate knowledge could marry early 7,532 times compared to respondents who have good knowledge. The importance of providing adolescents with information and health education about early marriage, in which parents also play a critical role in parenting patterns, including preventing the possibility of early marriage.